The role of brand trust as a mediator in the relationship between brand awareness, social media marketing, and brand loyalty - Fadhilah Fauzi, Nailatul; Evanita, Susi (Universitas Negeri Padang, 2024)
This study aims to investigate the effects of brand awareness and social media marketing on brand loyalty, with brand trust as a mediating variable, at Hai Coffee Padang Panjang. The population consists of Hai Coffee Padang Panjang customers, with a sample size of 170 respondents. Data were collected using questionnaires and analyzed using SmartPLS4. The results indicate that: (1) brand awareness has a positive and significant effect on brand trust; (2) social media marketing does not have a positive and significant effect on brand trust; (3) brand awareness has a positive and significant effect on brand loyalty; (4) social media marketing does not have a positive and significant effect on brand loyalty; (5) brand trust has a positive and significant effect on brand loyalty; (6) brand awareness has a positive and significant indirect effect on brand loyalty through brand trust; and (7) social media marketing does not have a positive and significant indirect effect on brand loyalty through brand trust.